Physical Fitness Level of Junior High School Football Club Students of Medan Amal Bakti Foundation Age Group 13 -14 Years - Aritonang Oppu Sunggu, Gidion; Sari, Liliana Puspa (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Using a method that is in accordance with the objectives to be achieved is an absolute requirement needed in a research process. This research is a descriptive research. Descriptive research is research that does not intend to test hypotheses, but only describes what is the condition of a variable. Data collection method is a method used by researchers in collecting research data. The method used in this study is a survey method with test and measurement techniques. This research will be carried out in the even semester of 2021 at the Amal Bakti Medan Middle School Football Club Age Group 13-14 for the 2020/2021 Academic Year. Variable is something that is used as a characteristic, trait or measure that is owned or obtained by a research unit in a thesis about a certain concept of meaning. So the research variables are objects that are experienced, analyzed and concluded in a research observation. Most of the physical fitness levels of club Football Yayasan Amal Bakti Medan Age 13 -14 years are in the good category. In detail, 0 students (0%) were in the very poor category, 7 students (23.33%) were in the poor category, 7 students (23.33%) were in the moderate category, 12 students (40%) were in the good category, and 4 students (13 .33%) in the very good category. Most of the frequency is in the good category, thus the physical fitness level of the Amal Bakti Medan Middle School Soccer Club students in the Age Group 13-14 for the 2020/2021 Academic Year is mostly in the good category.